A phenomenological investigation into potassium migration and ash sintering characteristics during p.f. combustion of lignites with and without K2CO3 addition. (5th February 2019) - Zhang, Jiguang; Li, Jianbo; Zhu, Mingming; Zhang, Zhezi; Zhou, Baozhong; Shen, Guoqing; Zhang, Dongke
Highlights: Migration of K and its role in sintering of lignite ashes systematically studied. Sintering temperature increased with increasing combustion temperature. Sintering temperature was decreased when K2 CO3 was added into the lignites. K was involved into mineral interaction even at 423 K in plasma asher. DTF ashes rich in Al2 O3 were not sintered even if 10 wt% K2 CO3 was added. Abstract: The morphology, mineralogy, and sintering characteristics of different lignite ashes prepared at varying temperatures in various lab-scale furnaces were investigated concerning the effect of K2 CO3 addition. Lignites with and without K2 CO3 addition were oxidised in a plasma asher at 423 K, a muffle furnace at 1073 K and a drop tube furnace (DTF) at 1773 K. Sintering temperatures of the ashes were determined, and their mineralogical and morphological features were analysed using XRD and SEM-EDS. Results showed that ash sintering temperature was increased as combustion temperature increased but decreased as K2 CO3 addition ratio increased. Moreover, sintering temperatures of ashes rich in alumina oxide were the highest among the lignite ashes prepared at the same temperature. This trend remains valid for ashes of K2 CO3 -doped lignites. SEM-EDS results revealed that ashes from plasma asher were irregular and loose whereas the DTF ashes of the K2 CO3 -doped lignites were mostly spherical in shape, having incurred severe sintering. The lignite ashes from plasma asher tended to be enriched in boehmite and arcanite. At 1723 K as in DTF, new mineral phases including mullite and kalsilite were detected. When K2 CO3 was added into lignites, kalsilite, microcline, and potassium sulphate of low melting-points were identified, consequently decreased ash sintering temperature.